CONSTRUCTIVE ENGAGEMENT INDONESIA DALAM MENDUKUNG KEBERLANGSUNGAN DEMOKRASI DI MYANMAR - Windy Dermawan (JWP (Jurnal Wacana Politik), 2016)
As a country which has attention to democracy and human rights, also has the strategic role of Indonesia in regional and international level, Indonesia has a political will to help Myanmar in continuing the survival of democracy there. Through the values which upheld ASEAN, namely the principle of non-intervention, Indonesia seeks to use constructive engagement approach, which emphasizes consensus and avoid confrontation with the inclusive spirit and persuasive attention. Indonesia’s efforts shaped positive support by promoting diplomatic role, involvement in co-operation, foreign aid presence in the investment, dialogue, and exchange of ideas related to a variety of issues. This approach is diametrically opposed to a boycott or embargo to turn Myanmar into a democratic state.